2013
DOI: 10.1177/1090820x12469807
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Accuracy and Reproducibility of Portrait 3D Surgical Simulation Platform in Breast Augmentation

Abstract: The Portrait 3D breast imaging system provides a highly reproducible 3D tool for measuring breast volume and simulating breast augmentation. Accuracy of the 3D models can vary up to 30% (mean 12.2%). This variability should be accounted for when using this technology to visually communicate with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Recently, commercially available 3D devices also enable the surgeon to model the pre-operative 3D surface image by choosing varying implant sizes and implant contours [45], [46]. But these solutions apply a non-physical morphing approach, and the studies suffer from a lack of sufficient clinical validation as the results are either compared to postoperative scans 6 weeks after surgery [46] or breast surface morphing starts from the 3D surface image solely without taking the thoracic wall as the correct anatomical rear boundary into account [46], [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, commercially available 3D devices also enable the surgeon to model the pre-operative 3D surface image by choosing varying implant sizes and implant contours [45], [46]. But these solutions apply a non-physical morphing approach, and the studies suffer from a lack of sufficient clinical validation as the results are either compared to postoperative scans 6 weeks after surgery [46] or breast surface morphing starts from the 3D surface image solely without taking the thoracic wall as the correct anatomical rear boundary into account [46], [47].…”
Section: Discussionmentioning
confidence: 99%
“…But these solutions apply a non-physical morphing approach, and the studies suffer from a lack of sufficient clinical validation as the results are either compared to postoperative scans 6 weeks after surgery [46] or breast surface morphing starts from the 3D surface image solely without taking the thoracic wall as the correct anatomical rear boundary into account [46], [47]. As we have demonstrated in a previous study, changes in breast contour and volume after augmentation mammaplasty caused by postoperative soft tissue swelling are completed not earlier than after 3 months [23].…”
Section: Discussionmentioning
confidence: 99%
“…stripe, grid, or dots) and captures the distortion in the light pattern using multiple calibrated cameras to derive at 3D surface data (27,31). Axis Three Torso System (Axis Three, Miami, FL, USA) is the most frequently reported structured light 3D scanner and has demonstrated its accuracy and reliability in simulating breast augmentation outcomes (32). However, it has not been studied in autologous breast reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, reports using 3D photography, also known as 3D scanning or surface imaging, for volumetric analysis in breast reconstruction has been growing (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Compared to the conventional imaging modalities, such as CT scans, 3D photography forgoes radiation exposure and a growing number of investigators have demonstrated its accuracy and reliability in breast application (26)(27)(28)32,(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation